Small animal PET imaging using GATE Monte Carlo simulations : Implementation of physiological and metabolic information - Silva, Susana Evaristo de Oliveira Branco, 1978- (2010)
Tese de doutoramento, (Engenharia Biomédica e Biofísica), Universidade de Lisboa, Faculdade de Ciências, 2010